Temperature monitoring for quality management in Cold Chain - Kumar , Sanoj (Journal of Postharvest Technology, 2021)
Time temperature indicators are devices which integrate the exposure to temperature over time by accumulating the effect of such exposures and exhibiting a change of colour (or other physical characteristic). TTI’s are commonly used in food, pharmaceutical and medical products to indicate exposure to excessive temperature abuse. TTI’s help in assure the cool chain of food products, they are expected to reduce the amount of food waste, as well as reducing the number of food borne illnesses. The mandatory regulations on pharmaceutical cold chain logistics by international and national associations like WHO are influencing the demand for TTI labels. Global time temperature indicator labels market is expected to witness rapid growth during the forecast period. This growth is expected to be primarily driven by growing concern about food wastage and its impacts on economy.